Local and global superconductivity in bismuth: Сверхпроводимость и сверхтекучесть - Baring, Luis A.; Silva, Robson R. da; Kopelevich, Yakov (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
We performed magnetization M(H,T) and magnetoresistance R(T,H) measurements on powdered (grain size ~ 149 μm) as well as highly oriented rhombohedral (A7) bismuth (Bi) samples consisting of single crystalline blocks of size ~ 1×1 mm in the plane perpendicular to the trigonal c axis. The obtained results revealed the occurrence of (1) local superconductivity in powdered samples with Tc(0) = (8.75 ± 0.05) K, and (2) global superconductivity at Tc(0) = (7.3 ± 0.1) K in polycrystalline Bi triggered by low-resistance ohmic contacts with silver(Ag) normal metal. The results provide evidence that the superconductivity in Bi is localized in a tiny volume fraction, probably at intergrain or Ag/Bi interfaces. On the other hand, the occurrence of global superconductivityobserved for polycrystalline Bi can be accounted for by enhancement of the superconducting order parameter phase stiffness induced by the normal metal contacts, the scenario proposed in the context of “pseudogap regime”in cuprates [E. Berg et al., Phys. Rev. B78, 094509 (2008)].